ORGANOLEPTIC QUALITY OF BROILER MEAT SUBTITUTED MAGGOTS IN COMMERCIAL RATIONS - I M., Wirawan; Astawa, I P. A.; Oka, A.A. (Jurnal Peternakan Tropika, 2024)
The study aims to find out the impact of the use of Black Soldier Fly Maggot (Hermetia illucens) subtituted into commercial ransom on the organoleptic quality of broiler meat. The research was conducted in the village of Nyitdah, Kediri district, Tabanan district for eight weeks from September – November 2022 using a complete random scheme consisting of four treatments and four repetitions where each repeat consists of four broilers. Treatment consists of P0 (without the addition of maggot weed), P1 (5% maggot), P2 (10% maggot), P3 (15% maggot). The scheme used in this study was a complete random scheme (RAL) with 4 treatments and 4 repetitions each consisting of four broiler tails. The variables observed are color, aroma, texture, taste, and overall reception. The results of the study showed that the subtitling of maggot helmet into the slice to the organoleptic qualities of broiler meat was a real difference (P<0,05) in terms of color, aroma, texture and overall reception, while on appearance and taste there were no real differences (P>0,05). From the results of the study, it can be concluded that the subtitling of 5 %, maggot veal can improve the organoleptic quality of broiler meat in terms of color, aroma, texture, and overall reception, but does not affect the appearance and taste.